Determinação da tenacidade à fratura do Aço API-X65 utilizado em tubos na indústria de petróleo e gás - Soares, Polliana Alexandre (2011)
This work was developed in order to determine the fracture toughness in structures containing cracks in its welds. The material tested was the API X65 steel tubes which is used in industry for the production of oil and gas, for example. The tube has a diameter of 20 inches with a thickness of 6.8 mm. We studied two different conditions: material "base metal" and "weld metal", and for each condition were tested nine and eight specimens, respectively. The welding process used was the Electrical Resistance Welding (ERW). The specimens were prepared according to ASTM E 1820-01 and the criterion of fracture mechanics was employed Resistance Curve (R Curve), which provides maximum aperture size and the crack occurs without rupture of the material. The fracture toughness was observed and the base metal and weld metal showed the same values of this property. Through scanning electron microscopy (SEM), it may be noted that the fracture is ductile and has wells (dimples) and inclusions. Under optical microscopy, it is seen that the steel API X65 in the base metal has a perlitic-ferritic structure with fine grains in the weld metal and increases the grain size.